Recent advances in the synthesis of smart hydrogels. Issue 14 (23rd June 2021) - Sikdar, Partha; Uddin, Md. Mazbah; Dip, Tanvir Mahady; Islam, Shafiqul; Hoque, Md. Saiful; Dhar, Avik K.; Wu, Shuangyan
Abstract : Understanding the surrounding atmosphere and reacting accordingly with a precise action are always fascinating features of a material. Abstract : Understanding the surrounding atmosphere and reacting accordingly with a precise action are always fascinating features of a material. Materials that pose such responsiveness are called smart materials. Currently, research studies on smart materials are being accelerated exponentially around the world; this is also true for smart hydrogels. Smart hydrogels with various chemically and structurally responsive moieties exhibit excellent characteristics of reacting under different environmental conditions such as pH, temperature, light, electric field, and magnetic field as well as biological and chemical stimuli. These smart hydrogels are drawing the attention of researchers for a wide range of applications, for instance, in designing biomedical, industrial, agricultural, electrical, healthcare, and hygienic products. This review encompasses the latest developments in the field of smart hydrogel synthesis based on their unique features and different aspects of their responsive behaviors. Additionally, this paper covers some of the recent strategies for tuning special functional properties of smart hydrogels for targeted applications.